Analysis of The Influence of Price Policy, Promotion, and Supporting Facilities on Student Satisfaction at STIE Eka Prasetya Medan - Ezekiel Berliantoro Sitorus (PT PUSTAKA CENDEKIA PUBLISHER, 2025)
The purpose of this study is to analyze how pricing policies, promotions, and supporting facilities influence student satisfaction at STIE EKA PRASETYA. Multiple linear regression analysis, including F and t-tests, was used for evaluation. The research had 60 respondents, with the sample selected by an accidental sampling method. Data collecting method including the distribution of questionnaires and conducting interviews. Instrument testing employs validity and reliability assessments concurrently. Result From the calculation of the F test, the calculated F is 43.108 ≥ F table 2.44 with a p-value of 0.000 ≤ 0.05. In addition, the Adjusted R Square value is known to be 59.8%. Moreover, from the results of the t-test, it is known that partially, the variables of price, promo, and supporting facilities have a significant effect on the calculation of the calculated t of the price variable 3.195 ≥ t table 1.980; the calculated t value of the promotion attribute 2.508 ≥ t table 1.980; the t value of supporting facilities 4.188 ≥ t table. The variable with the dominant influence is the supporting facilities variable, with a contribution of 0.377.